Students’ Writing Anxiety and Its Implication to Local Context - Gina Selvira Yanti; Nurul Hidayati Hidayati (Politeknik Negeri Padang, 2021)
Writing anxiety has been considered a significant hindrance for most Indonesian EFL students. With a growing number of available literatures on this issue, this paper aims to grasp the trends and deliver some implications to the national and local context. The available researches are the ones that have been published from 2017 to 2021. The subjects in those researches are university students majoring in English department. This review is one of the steps in pre-research on students’ anxiety in research courses and it has been done by using scoping study method. Therefore, taken from the thirteen collected literature, the trends have been summed up into 1. Types and levels of writing anxiety; 2. Factors or causes of writing anxiety; 3. Strategies to reduce writing anxiety; 4. Implications. The findings show that cognitive anxiety, linguistic difficulties the dominant in the trends of types and factors of students writing anxiety. In respect to the level, the findings indicate that students have moderate to high anxiety levels while metacognitive and affective as the dominant strategies used by students. Thus, in general, the findings have strengthened the concept of writing anxiety as an obstacle in students’ writing skills. Overall, some other significant variables such as personality traits, teaching techniques, awareness, and affective factors should be taken in future studies, and practices in teaching writing.